2023
DOI: 10.1029/2022jd037660
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Characteristics of Radially Outward Propagating Tropical Cyclone Diurnal Pulses

Abstract: Tropical cyclones (TCs) are one of the most catastrophic natural hazards, causing thousands of deaths and billions of dollars in economic losses every year (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
(283 reference statements)
0
2
0
Order By: Relevance
“…Previous studies found that the initiation of the diurnal pulse is closely linked to a strong IR BT cooling signal within the inner core, which may imply the fast developing of the inner-core deep convection and the RI of TCs (X. Zhang et al, 2023;X. Zhang & Xu, 2021b).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies found that the initiation of the diurnal pulse is closely linked to a strong IR BT cooling signal within the inner core, which may imply the fast developing of the inner-core deep convection and the RI of TCs (X. Zhang et al, 2023;X. Zhang & Xu, 2021b).…”
Section: Methodsmentioning
confidence: 98%
“…The inner‐core IR BT cooling rate represents how fast the convection is developing (Dunion et al., 2014; X. Zhang & Xu, 2021b). Previous studies found that the initiation of the diurnal pulse is closely linked to a strong IR BT cooling signal within the inner core, which may imply the fast developing of the inner‐core deep convection and the RI of TCs (X. Zhang et al., 2023; X. Zhang & Xu, 2021b). The surface precipitation can be a proxy of the convection through the deep layer of the troposphere (Leppert & Cecil, 2016; X. Zhang & Xu, 2022).…”
Section: Methodsmentioning
confidence: 98%